2017
DOI: 10.3892/or.2017.5574
|View full text |Cite
|
Sign up to set email alerts
|

Maspin suppresses growth, proliferation and invasion in cutaneous squamous cell carcinoma cells

Abstract: Cutaneous squamous cell carcinoma (cSCC) is a common malignant tumor. Mammary serine protease inhibitor (Maspin), a member of serpin family, has been reported as a tumor suppressor in various carcinomas. In this study, we detected the expression level of Maspin in cSCC tissues by real-time PCR and western blotting, and found that Maspin was downregulated in the cSCC tissues compared with the adjacent normal tissues. Moreover, Maspin was stably overexpressed in A431 cells, and CCK-8 assay, colony formation assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Although bioinformatics tools predicted multiple miR-21 targets, we focused on PDCD4 and Maspin, both tumor suppressors, as they are known to regulate cell proliferation and/or migration (Wang et al, 2015;H. Zhu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although bioinformatics tools predicted multiple miR-21 targets, we focused on PDCD4 and Maspin, both tumor suppressors, as they are known to regulate cell proliferation and/or migration (Wang et al, 2015;H. Zhu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Although bioinformatics tools predicted multiple miR‐21 targets, we focused on PDCD4 and Maspin, both tumor suppressors, as they are known to regulate cell proliferation and/or migration (Wang et al, 2015; H. Zhu et al, 2017). Furthermore, the expression of PDCD4 and Maspin was found to be consistent with the regulation pattern of miR‐21, both in the clinical samples as well as in the miR‐21 mimic/antagomiR transfected cells, thus confirming them to be targeted by miR‐21.…”
Section: Discussionmentioning
confidence: 99%
“…Studies performed on A431 cell line revealed that overexpression of Maspin inhibits growth, cellular proliferation and enhances A431 cells apoptosis by increasing PARP and Bax expression, while decreasing Bcl-2 expression. Therefore, Maspin analysis may provide new insights in the diagnosis and therapy of cSCC [93].…”
Section: Current and Future Molecular Therapeutic Targets In Cutaneous Sccmentioning
confidence: 99%
“…SerpinB5 was expressed in normal breast epithelial cells, skin, prostate, testis, lung, tongue, intestine and thymus, but the expression level was abnormally lower in a variety of malignant tumors compared with the expression level in normal tissue. Previous studies have shown that SerpinB5 can inhibit the occurrence and development of tumors, including promoting tumor cell apoptosis, inhibiting tumor angiogenesis, and inhibiting tumor metastasis (18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%